2020
DOI: 10.1016/j.heliyon.2020.e03267
|View full text |Cite
|
Sign up to set email alerts
|

The cultural practices of Bamar diabetic patients: An ethnographic study

Abstract: Background: Many qualitative studies on the feelings and lived experiences of diabetic patients have already been conducted in European and Asian countries. However, little is known about the cultural practices of diabetic patients among the Bamar population of Myanmar. Aim: The aim of this study was to explore the cultural practices of Bamar diabetic patients in Myanmar. Methods: The conceptual framework of this ethnographic study was based on Spradley's ethnographic theory and Leininger's cultural care theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Participants also stated believing that DM can be cured by self-management and by God's will. This corresponds to the results of a study in Myanmar, which found participants believed diabetes could be cured completely through the use of traditional medicine [ 23 ]. While such positive thinking may benefit DM patients, health care providers should educate their patients about the cause and management of the disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants also stated believing that DM can be cured by self-management and by God's will. This corresponds to the results of a study in Myanmar, which found participants believed diabetes could be cured completely through the use of traditional medicine [ 23 ]. While such positive thinking may benefit DM patients, health care providers should educate their patients about the cause and management of the disease.…”
Section: Discussionsupporting
confidence: 86%
“…For example, an African American may refuse to use insulin because of a cultural view that insulin can cause diabetes complications and damage to organs [ 20 , 21 ]. Culture can also make patients choose traditional remedies over modern medicine, as has been seen in Mexico, and Myanmar [ 22 , 23 ]. Cultural beliefs have been shown to lead to raised blood glucose levels [ 24 ], and to promote fatalistic beliefs about diabetes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the calorie intake using mobile applications, reducing food portion and avoiding sweetened foods and beverages were common practices which are in line with the common dietary recommendations for young people with T2DM (11). Meanwhile, the strategies in rice intake are in agreement with the previous research conducted in Asian countries; where rice is a staple food in these countries (35,39). Nevertheless, the foreign investment in the food industry, unfettered marketing of processed foods and the wide accessibility and affordability of unhealthy foods and beverages can potentially lead to uncontrolled consumption thus increased the risk of T2DM complications among the young patients (40).…”
Section: Discussionsupporting
confidence: 78%
“…Few participants also believed that diabetes could be cured through herbal remedies and that home remedies could help reduce blood glucose levels. The use of vegetables as home remedies to bring down blood glucose levels and relieve symptoms was also been reported in the study conducted by Wah Oo et al 42 in Myanmar. Similarly, in their study to find the common herbs used by the village people of Kerala for curing diabetes mellitus, Jasna et al 43 found guava leaf, fenugreek, neem, gooseberry, curry leaves, ladies' finger, leaves of passion fruit, turmeric, ginger, and spinach were the common herbs reported to be used by the people.…”
Section: Discussionmentioning
confidence: 54%
“…Religiosity and spirituality act as coping mechanisms among people living with diabetes because it has been found that people with high religiosity could lower their blood glucose levels but not those with low religiosity. 40 In their ethnographic study in Myanmar, Wah Oo et al 42 reported similar findings where spiritual and religious beliefs act as coping mechanisms for diabetes. However, van Houtum 53 argues that religion can dictate a lifestyle or habits that harm an individual’s health or complicate existing illnesses.…”
Section: Discussionmentioning
confidence: 80%